Characterization of mesothelin gene expression in dogs and overexpression in canine mesotheliomas - Nabeta, Rina; Kanaya, Ami; Shimada, Kazumi; Matsuura, Katsuhiro; Yoshimura, Aritada; Oyamada, Tomohiro; Azakami, Daigo; Furuya, Tetsuya; Uchide, Tsuyoshi (Frontiers in Veterinary Science, 2024)
IntroductionCanine mesotheliomas are uncommon malignant tumors typically detected late. Minimally invasive diagnostic biomarkers would facilitate diagnosis at earlier stages, thereby improving clinical outcomes. We hypothesized that mesothelin could be used as a reliable diagnostic biomarker for canine mesotheliomas since it has been used as a cancer biomarker for human mesothelioma. We aimed to explore and characterize mesothelin gene expression in dogs and assess its use as a diagnostic biomarker for canine mesotheliomas.Materials and methodsWe quantified expressed canine mesothelin transcripts via reverse transcription polymerase chain reaction (RT-PCR) and sequenced them using ribonucleic acid (RNA) extracted from a canine mesothelioma cell line. After confirming mesothelin expression, we assessed its levels in major organ tissues and compared them with those in the mesothelioma tissues using quantitative PCR (qPCR). Mesothelin overexpression in mesotheliomas was detected, and we further compared its levels using qPCR between mesotheliomas and non-mesotheliomas using tumor tissues and clinical sample effusions, confirming its significance as a diagnostic biomarker for canine mesothelioma.ResultsMesothelin complementary deoxyribonucleic acid (cDNA) was amplified via RT-PCR, yielding a single band of expected upon DNA electrophoresis. Sequence analyses confirmed it as a predicted canine mesothelin transcript from the genome sequence database. Comparative sequence analysis of the deduced amino acid sequence of the expressed canine mesothelin demonstrated molecular signature similarities with the human mesothelin. However, the pre-sequence of canine mesothelin lacks the mature megakaryocyte potentiating factor (MPF) portion, which is typically cleaved post-translationally with furin. Mesothelin expression was quantified via qPCR revealing low levels in the mesothelial and lung tissues, with negligible expression in the other major organs. Canine mesothelin exhibited significantly higher expression in the canine mesotheliomas than in the noncancerous tissues. Moreover, analysis of clinical samples using qPCR demonstrated markedly elevated mesothelin expression in canine mesotheliomas compared to non-mesothelioma cases.Discussion and conclusionCanine mesothelin exhibits molecular and biological characteristics akin to human mesothelin. It could serve as a vital biomarker for diagnosing canine mesotheliomas, applicable to both tissue- and effusion-based samples.